PENGARUH STRATEGI INOVASI PRODUK TERHADAP LOYALITAS PELANGGAN: PENGARUH STRATEGI INOVASI PRODUK - Silfani Arfita Utami Arfah; Esti Kiki Riski Sukran; Wiwin Sultraeni (JAMB:Journal of Digital Business and Management, 2026)
This study aims to analyze the influence of product innovation strategy on customer loyalty in the face of increasingly competitive markets. Product innovation is viewed not merely as an aesthetic endeavor, but as a strategic instrument for maintaining relevance and meeting evolving consumer needs. The research method used was quantitative, with simple linear regression analysis on a sample of 120 respondents. Data was collected to test the extent to which innovation variables, including feature updates, quality, and design, can boost long-term customer commitment. The statistical analysis results indicate that product innovation strategy has a positive and significant influence on customer loyalty. This is evidenced by the t-value of 8.560 with a significance level of 0.000. The regression equation Y = 8.420 + 0.645X indicates that every increase in the innovation variable will be followed by a linear increase in customer loyalty. The findings also revealed a coefficient of determination (R2) of 0.412, meaning product innovation contributed 41.2% to loyalty, while the remaining 58.8% was influenced by other external factors such as brand image and service quality. The novelty of this study highlights the shift in consumer behavior, which is now more sensitive to functional innovation and product performance than simply physical design. Pragmatic consumers tend to have an emotional attachment to products that provide real solutions through technological advances. Theoretically, these results support the literature stating that failure to innovate will lead to a loss of market relevance. Practically, companies are advised to make functional innovation the foundation of customer trust while optimizing other supporting variables. These findings confirm that the integration of product value innovation and understanding consumer needs is key to creating a holistic and sustainable customer retention strategy amidst the dynamics of the modern industry.